Estimation of different forest-related contributions to the radiative balance using observations in southern Finland - Kurtén, T.; Kulmala, M.; Dal Maso, M.; Suni, T.; Reissell, A.; Vehkamäki, H.; Hari, P.; Laaksonen, A.; Viisanen, Y.; Vesala, T. (Boreal Environment Research Publishing Board, 2024)
The effect of boreal forest on the Earth's energy budget was estimated in field conditions in Hyytiälä, southern Finland. The indirect aerosol effect due to new particle formation, the effect of forest carbon sequestration and the effect of forestation- or deforestation-related albedo change were investigated. The young, fast-growing boreal forest was estimated to be a relatively significant carbon sink and an important aerosol source, and thus the effect on the Earth's energy budget was seen to be negative. The estimated values (reported as annually averaged energy budget perturbations per square meter of forest) were –36 W m–2 due to the carbon sink, +10 W m–2 due to the albedo effect and between –5 and –14 W m–2 due to the aerosol effect. However, the values are uncertain.